2018
DOI: 10.1016/j.devcel.2017.12.024
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiomyocytes Sense Matrix Rigidity through a Combination of Muscle and Non-muscle Myosin Contractions

Abstract: SummaryMechanical properties are cues for many biological processes in health or disease. In the heart, changes to the extracellular matrix composition and cross-linking result in stiffening of the cellular microenvironment during development. Moreover, myocardial infarction and cardiomyopathies lead to fibrosis and a stiffer environment, affecting cardiomyocyte behavior. Here, we identify that single cardiomyocyte adhesions sense simultaneous (fast oscillating) cardiac and (slow) non-muscle myosin contraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 87 publications
5
99
0
Order By: Relevance
“…In this respect, completely crosslinked hydrogels fabricated using three different compositions of biomaterial inks (by varying the amount of GelMA) were analyzed for their compressive strength in order to finalize the optimal concentration of the supporting hydrogel (Figure C,D). In particular, a Young's modulus of 37.3 ± 4.9 kPa was obtained for ink comprising of 5% GelMA, 1% n‐SF and 1% PEGDMA (SPG5) that was in the range of the local modulus of native ECM . The ability to assure the viability of the encapsulated cells in polymer‐based hydrogels requires them to be porous enough that an exchange of nutrients and oxygen can be facilitated.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, completely crosslinked hydrogels fabricated using three different compositions of biomaterial inks (by varying the amount of GelMA) were analyzed for their compressive strength in order to finalize the optimal concentration of the supporting hydrogel (Figure C,D). In particular, a Young's modulus of 37.3 ± 4.9 kPa was obtained for ink comprising of 5% GelMA, 1% n‐SF and 1% PEGDMA (SPG5) that was in the range of the local modulus of native ECM . The ability to assure the viability of the encapsulated cells in polymer‐based hydrogels requires them to be porous enough that an exchange of nutrients and oxygen can be facilitated.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed, this was shown by Stout et al, presenting a change in cellular adhesion characteristics based on a synergistic mix of topography and stiffness brought on by CNF doping. An interesting work by Pandey et al illustrates the way native heart tissue mechanical cues induce proliferation, differentiation or fibrosis. It can be inferred that a hierarchy of mechanical cues, simulated by a soft substrate with stiff components, may also be beneficial to cellular growth.…”
Section: Discussion and Open Questions For The Use Of Conductive Tissmentioning
confidence: 99%
“…It has very recently been reported that Fhod1 is involved in mechanosensing of matrix rigidity in cultured cardiomyocytes via regulation of nonmyofibrillar contractions (Pandey et al, ). Considering that Fhod1 is only marginally expressed in the normal heart tissue (as shown here), it may be possible that Fhod1 expression is induced during isolation and/or culture of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%